Review: Margarete Jäger & Siegfried Jäger (2007). Deutungskämpfe. Theorie und Praxis Kritischer Diskursanalyse [Fighting About Meaning. Theory and Practice of Critical Discourse Analysis] - Hirseland, Andreas (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
The book presents an overview of the theoretical foundation of Critical Discourse Analysis and its empirical application in the field of the analysis of media- and everyday discourses. It focuses particularly on the areas of migration, racism and biopolitics. The review note mainly discusses the question of the theoretical reasoning of critical discourse orientation and its methodological implementation. The question is opened up as to whether a critical position can be founded on FOUCAULT's theory of discourse alone. Regarding the methodological approach, the lack of criteria for the validity of data analysis is criticized—thus addressing a problem that is not yet solved in the field of discourse analysis in general.URN: urn:nbn:de:0114-fqs0702274